Dangerous encounters-- avoiding perilous situations with autism : a streetwise guide for all emergency responders, retailers, and parents - Davis, Bill, 1953- (Jessica Kingsley Publishers, 2002)
'Bill masterfully translates and suggests how to interpret common behaviors of people with autism for law enforcers, rescue personnel and other first responders. However, all people desiring a deeper understanding in making the world a safer and more understandable place for people with autism will benefit greatly from reading Dangerous Encounters . Bill's use of indoor shopping malls and other everyday surroundings for learning vital social skills are just some of the brilliant tools mentioned for parents and others working with people on the autism spectrum.'. - Stephen M. Shore, Board of Di.